Broad-Spectrum Cephalosporin-Resistant Klebsiella spp. Isolated from Diseased Horses in Austria - Loncaric, Igor (Animals (Basel), 2020)
SIMPLE SUMMARY: Broad-spectrum cephalosporin-resistant Klebsiella pneumoniae is considered as a serious problem for public human health. To date, only a few broad-spectrum cephalosporin-resistant Klebsiella have been isolated from horses. Considering the zoonotic potential of the Klebsiella spp., and the close relationship between man and horse, this study intended to generate data on the genetic background of broad-spectrum cephalosporin-resistant Klebsiella spp. isolated from horses in Austria. Overall, samples isolated between 2012 and 2019 from 1541 horses underwent bacteriological testing, resulting in 51 specimens tested positive for Klebsiella ssp. Antimicrobial susceptibility tests revealed that seven Klebsiella ssp. isolates were not only cefotaxime-resistant but also showed resistance against other classes of antibiotics so that they were considered to be multidrug-resistant. Data from whole genome sequencing and mating experiments strongly suggest that the majority of antibiotic resistance genes is encoded on plasmids in these seven multidrug-resistant Klebsiella ssp. Considering the potential threat when commensal Klebsiella inhabiting a healthy human gut acquire new antibiotic resistances due to the exchange of plasmids with multidrug-resistant Klebsiella ssp. from horses, further monitoring of horses and other domestic animals for the presence of broad-spectrum cephalosporin-resistant Klebsiella, not only in Austria but worldwide is therefore advisable. ABSTRACT: The aim of the present study was to investigate the diversity of broad-spectrum cephalosporin-resistant Klebsiella spp. isolated from horses in Austria that originated from diseased horses. A total of seven non-repetitive cefotaxime-resistant Klebsiella sp. isolates were obtained during diagnostic activities from autumn 2012 to October 2019. Antimicrobial susceptibility testing was performed. The isolates were genotyped by whole-genome sequencing (WGS). Four out of seven Klebsiella isolates were identified as K. pneumoniae, two as K. michiganensis and one as K. oxytoca. All isolates displayed a multi-drug resistant phenotype. The detection of resistance genes reflected well the phenotypic resistance profiles of the respective isolates. All but one isolate displayed the extended-spectrum β-lactamases (ESBL) phenotype and carried CTX-M cefotaximases, whereas one isolate displayed an ESBL and AmpC phenotype and carried cephamycinase (CMY)-2 and sulfhydryl variable (SHV)-type b and Temoniera (TEM) β-lactamases. Among Klebsiella pneumoniae isolates, for different sequence types (ST) could be detected (ST147, ST307, ST1228, and a new ST4848). Besides resistance genes, a variety of virulence genes, including genes coding for yersiniabactin were detected. Considering the high proximity between horses and humans, our results undoubtedly identified a public health issue. This deserves to be also monitored in the years to come.